Constructivism: Man versus Environment : International major event concerning contemporary constructivism. - Ilgen, Fré; Ilgen-van Rooijen, Jacqueline; Gunst, Ronald; Hengeveld, Pim; de Thouars, Alexandre (Dordrecht : Stichting PRO, 1989)
Biederman, Charles ; Edmonds, Ernest ; Elders, Fons ; Flusser, Vilém ; Hölzinger, Johannes Peter ; Horvers, Toine ; Ilgen, Fré ; Infante, Francisco ; Mahlow, Dietrich
special projects ## Husquinet, Jean Pierre, Belgium ## Cabodi, Gilles, Belgium ## Mosso, Leonardo - Prof. Arch., Italy ## Tebby, Susan - PhD, Great Britain
Constructivism: Man versus Environment, World Trade Center, Rotterdam, 29 09 - 02 10 1989
kunstcatalogus